2006
DOI: 10.1128/aac.50.1.344-347.2006
|View full text |Cite
|
Sign up to set email alerts
|

5-Nitroimidazole Drugs Effective against Metronidazole-Resistant Trichomonas vaginalis and Giardia duodenalis

Abstract: Metronidazole (Mz)-resistant Giardia and Trichomonas were inhibited by 1 of 30 new 5-nitroimidazole drugs.Another five drugs were effective against some but not all of the Mz-resistant parasites. This study provides the incentive for the continued design of 5-nitroimidazole drugs to bypass cross-resistance among established 5-nitromidazole antiparasitic drugs.Metronidazole (Mz) and a related 5-nitroimidazole, tinidazole, are the only drugs recommended for the treatment of trichomoniasis and are the most-prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 21 publications
6
101
0
1
Order By: Relevance
“…The nitro group is critical for antimicrobial activity, whereas the 3-position cannot be functionalized without fundamentally altering the core heterocycle, leaving the 1-, 2-, and 4-positions for potential modifications to improve activity. Prior studies on side chain modifications had not revealed any clear structural themes that could be exploited to generate compounds with superior activity (4,13). As an alternative, we reasoned that generating broad unbiased structural diversity might be more powerful than incremental optimization for developing improved antimicrobials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitro group is critical for antimicrobial activity, whereas the 3-position cannot be functionalized without fundamentally altering the core heterocycle, leaving the 1-, 2-, and 4-positions for potential modifications to improve activity. Prior studies on side chain modifications had not revealed any clear structural themes that could be exploited to generate compounds with superior activity (4,13). As an alternative, we reasoned that generating broad unbiased structural diversity might be more powerful than incremental optimization for developing improved antimicrobials.…”
Section: Resultsmentioning
confidence: 99%
“…These modifications mostly affect the pharmacokinetic properties of the drugs but have only limited influence on drug potency or ability to overcome resistance (9). However, other structural modifications of 5-NI compounds can improve antimicrobial activity and resistance profiles (4,13) or confer new antimicrobial activities, as shown for the kinetoplastid Trypanosoma Significance Drugs against disease-causing microbes are among the major achievements of modern medicine, but many microbes show a tenacious ability to develop resistance, so they are no longer killed by available drugs. We show here for an important class of these drugs, represented by the common drug metronidazole, that broad modifications of the basic drug structure can improve drug activities against several clinically important microbes and unexpectedly overcome different forms of resistance.…”
mentioning
confidence: 99%
“…Although the cure rate was high, these drugs demonstrated treatment failure which was normally related to non-compliance because of side effects such as headache, dry mouth, metallic taste, glossitis, and urticaria caused by lengthy treatment or high doses (Garduño-Espinosa et al, 1992;Kapoor et al, 1999;Oxberry et al, 1994), or reinfection (Rocha et al, 2012). Moreover, an increasing number of metronidazole-resistant T. vaginalis isolates have been reported since metronidazole was introduced for the treatment of trichomoniasis in 1959 (Blaha et al, 2006;Butler et al, 2010;Durel et al, 1967;Narcisi & Secor, 1996;Schmid et al, 2001; Upcroft et al, 2006). In addition, the metronidazole-resistant isolates were cross-resistant to other members of the 5-nitrothiazole compounds including ornidazole, tinidazole, nitazoxanide, and furazolidone (Wright et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This was despite the general recognition that metronidazole is difficult to administer in children: it generally needs to be administered as 3-times daily for 10 days and has a bitter metallic taste, particularly when tablets have to be divided as no standard oral pediatric liquid formulation is available [7,8]. Metronidazole also induces adverse effects and resistance occurs in G. lamblia [8][9][10][11]. Notably, about three-quarters (72.0%) of pediatricians considered that the availability of a liquid formulation of nitazoxanide would change their potential treatment choice for diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Giardiasis is commonly treated with metronidazole or tinidazole; however, the tablet formulations can be difficult to administer in children because of pediatric dose requirements, possess an unpalatable metallic taste, and may cause adverse effects such as nausea [7,8]. In addition, resistance has been documented in G. lamblia [9][10][11]. Apart from nitazoxanide, there is no other commonly recommended specific treatment for cryptosporidiosis.…”
Section: Introductionmentioning
confidence: 99%